Beneath the Waves - Wu, Norbert; Nang Chan Yeema (Hong Kong Chronicle Books, 1992)
Describes plants and animals that live in and around kelp bed forests, including otters, seals, plankton, eels, and octopi.
Keywords: Juvenile Nonfiction